2004
DOI: 10.1242/jeb.01169
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in Palestine sunbirds: elimination of excess water does not constrain energy intake

Abstract: SUMMARY Although the renal responses of birds to dehydration have received significant attention, the consequences of ingesting and processing large quantities of water have been less studied. Nectar-feeding birds must often deal with exceptionally high water intake rates in order to meet their high mass-specific energy demands. Birds that ingest large volumes of water may either eliminate excess water in the kidney or regulate the volume of water absorbed in the gastrointestinal tract. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 41 publications
(75 reference statements)
3
36
0
Order By: Relevance
“…This has proven to be a distinct advantage of this protocol, and it has been widely applied recently (McWhorter and Martínez del Rio 1999;McWhorter et al 2003McWhorter et al , 2004McWhorter et al , 2006Hartman Bakken et al 2004;Hartman Bakken and Sabat 2006;Napier et al 2008b). Another advantage is that this method may be used to study the effects of diet energy density on the extent of paracellular absorption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This has proven to be a distinct advantage of this protocol, and it has been widely applied recently (McWhorter and Martínez del Rio 1999;McWhorter et al 2003McWhorter et al , 2004McWhorter et al , 2006Hartman Bakken et al 2004;Hartman Bakken and Sabat 2006;Napier et al 2008b). Another advantage is that this method may be used to study the effects of diet energy density on the extent of paracellular absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of l-glucose in the steady state feeding protocol (based on appearance of marker in excreta) is influenced by GFR, renal fractional water recovery (FWR), and rate of digesta passing through the intestine (McWhorter et al 2003). FWR is responsive to reduced water intake rate in red wattlebirds (Goldstein and Bradshaw 1998) and other nectarivorous birds (Hartman Bakken et al 2004;McWhorter et al 2004) while GFR has been shown to be responsive to more extensive water shortage (e.g., due to nocturnal fasting) in hummingbirds (Hartman Bakken et al 2004;Hartman Bakken and Sabat 2006); renal function in the nectarivorous birds studied to date may therefore be slowed or completely stop in response to reduced food (i.e., water) intake. When the birds are feeding ad lib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hummingbirds and many other migratory birds maintain very high glucose and elevated body fat as an adaptive trait without developing diabetes [24][25][26]. These birds consume high sugar food (nectar) and accumulate over 40% body fat shortly before migration, but they do not develop diabetes, polyurea, polyphagia, or polydipsia [27][28][29]. They have a very high metabolic rate and lose most of the stored fat in 20 hours by flying up to 600 miles across the Gulf of Mexico.…”
Section: Abbreviationsmentioning
confidence: 99%